Cama armónica digital (2014)
Inspired by some musical instruments used in music therapy, this degree work documents the development of a device capable of transmitting sound vibrations on the human body. Some studies show that the use of low frequency vibrations is beneficial to generate muscle relaxation states in the human body. The device consists of a table suitable to a soundboard and speaker system coupled wood. For understanding the vibrational phenomena in bed, acoustic strings, cavities, plaque and soundboards were studied. The sounds reproduced by the speaker system consists of the sum of two frequencies with a slight difference in the range, generating a pulse effect. These frequencies are in a range of 115-500Hz. An experimental study of the vibration modes of the stretcher showed that it would be possible to locate the points of stimulation in a body part through a fine adjustment of the frequencies reproduced. Since sound synthesis can be controlled from an external computer, this project contributes to future research on the influence of vibrations on human health.